Membangun Kepuasan Kerja melalui Pola Komunikasi Organisasi (Studi Kasus PT. Gorontalo Minerals) - Mohammad Hamdallah Ruchban; Moehammad Gafar Yoedtadi (Koneksi, 2026)
This study aims to analyze the organizational communication patterns between leaders and employees in building job satisfaction at PT Gorontalo Minerals. The research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation with nine informants, including company leaders and staff. Data analysis was conducted through the reduction, presentation, and conclusion-drawing stages, following the Miles and Huberman model, while data validity was strengthened through source and technique triangulation. The findings indicate that the company uses a chain-of-command pattern, reflecting a hierarchical organizational structure. Downward communication occurs through meetings, briefings, and work instructions, while upward communication occurs through performance reports and evaluations. Horizontal and diagonal communication also takes place for interdepartmental coordination, though it remains dominated by formal channels. Supporting factors for effective organizational communication include leadership openness, adequate communication facilities, and a collaborative work culture. Conversely, communication barriers consist of message distortion due to bureaucracy, differences in employees’ cultural backgrounds, and technical obstacles in the field. An open, clear, and participatory communication pattern has been proven to enhance job satisfaction, as reflected in increased motivation, loyalty, and productivity. This study affirms that the effectiveness of organizational communication is a key determinant in establishing a harmonious, productive, and adaptive work environment in the face of organizational change. Penelitian ini menganalisis pola komunikasi organisasi antara pimpinan dan karyawan dalam membangun kepuasan kerja di PT. Gorontalo Minerals. Menggunakan pendekatan kualitatif dengan metode studi kasus, data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi terhadap sembilan informan yang terdiri dari pimpinan dan staf. Analisis dilakukan dengan teknik reduksi, penyajian, dan penarikan kesimpulan secara induktif menggunakan model Miles dan Huberman, serta diuji validitasnya melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa perusahaan menerapkan pola komunikasi rantai yang mencerminkan struktur organisasi hierarkis. Komunikasi vertikal dari atas ke bawah dilakukan melalui rapat, briefing, dan instruksi kerja, sedangkan komunikasi dari bawah ke atas berlangsung melalui laporan dan evaluasi kinerja. Komunikasi horizontal dan diagonal juga terjalin untuk koordinasi lintas departemen, meskipun masih bersifat formal. Faktor pendukung utama komunikasi organisasi meliputi keterbukaan pimpinan, fasilitas komunikasi yang memadai, serta budaya kerja kolaboratif. Sebaliknya, hambatan komunikasi mencakup distorsi pesan akibat birokrasi, perbedaan latar belakang karyawan, dan kendala teknis di lapangan. Pola komunikasi yang jelas dan terbuka terbukti meningkatkan kepuasan kerja karyawan, yang ditandai dengan meningkatnya motivasi, loyalitas, dan produktivitas. Penelitian ini menegaskan bahwa efektivitas komunikasi organisasi merupakan determinan penting dalam menciptakan lingkungan kerja yang harmonis dan berorientasi pada kinerja, serta merekomendasikan penguatan komunikasi digital dan forum interaktif untuk meningkatkan responsivitas organisasi.